Front Cover: Simultaneous and Significant Improvements in Efficiency and Stability of Deep‐Blue Organic Light Emitting Diodes through Friedel‐Crafts Arylmethylation of a Fluorophore (ChemPhotoChem 5/2020). Issue 5 (28th April 2020) - Feng, Quanyou; Tan, Kesheng; Zheng, Xiaojun; Xie, Songlin; Xue, Kai; Bo, Yifan; Zhang, He; Lin, Dongqing; Rao, Junfeng; Xie, Xinmiao; Xie, Linghai; Cao, Hongtao; et al.
Abstract : The Front Cover image shows that excellent and comprehensive performances can be achieved for deep‐blue organic light emitting diodes (OLEDs) incorporating a fluorophore modified by Friedel–Crafts arylmethylation. More information can be found in the Communication by L. Xie, H. Zhang, W. Huang and co‐workers on page 321 in Issue 5, 2020 (DOI: 10.1002/cptc.201900268 ).